El Palacio : historiography and new perspectives on a pre-Tarascan city of northern Michoacán, Mexico - Forest, Marion, (Paris monographs in American archaeology ;, 2020)
11 contributions consider legacy and archive data (1896-1995) and results derived from recent archaeological investigations (2012-2017) to present a review and analysis of the chrono-stratigraphy, material culture, urbanism, and economic and ritual practices at El Palacio, northern Michoacán, Mexico, between A.D. 850 and 1521.